Immunogenicity of a Salmonella typhimurium aroA aroD Vaccine Expressing a Nontoxic Domain of Clostridium difficile Toxin A - Ward, Stephen J. (American Society for Microbiology, 1999)
The C-terminal repeat domain of Clostridium difficile toxin A harbors toxin-neutralizing epitopes and is considered to be a candidate component of a vaccine against C. difficile-associated disease (CDAD). Fourteen of the 38 C-terminal toxin A repeats (14CDTA) were cloned into pTECH-1 in frame with the immunogenic fragment C of tetanus toxin (TETC) to generate plasmid p56TETC. Expression of the TETC-14CDTA fusion protein was driven from the anaerobically inducible nirB promoter within attenuated Salmonella typhimurium BRD509 (aroA aroD). The TETC-14CDTA fusion protein was purified and shown to bind to known toxin A receptors found on the surface of rabbit erythrocytes. Intranasal (i.n.) and intragastric (i.g.) immunization with 10(7) and 10(10) CFU, respectively, of BRD509(p56TETC) generated significant (P < 0.05) anti-toxin A serum responses after a single dose. Antibody titers were elevated following a boosting dose with either live vaccine or a subcutaneous injection of 0.5 μg of purified 14CDTA protein. Importantly, serum from mice immunized with BRD509(p56TETC) neutralized toxin A cytotoxicity. Both i.n. and i.g. immunizations also generated toxin A-specific immunoglobulin A on the pulmonary and intestinal mucosa, respectively. Intranasal vaccination induced consistently higher serum and mucosal anti-toxin A antibody responses. Significant anti-tetanus toxoid serum and mucosal antibodies were also generated by both immunization routes. The availability of live attenuated Salmonella typhi for human use may allow the development of a multivalent mucosal vaccine against CDAD, tetanus, and typhoid.